Brassinosteroids Regulate Circadian Oscillation via the BES1/TPL-CCA1/LHY Module in Arabidopsisthaliana - Hong Gil Lee; Jin Hoon Won; Yee-Ram Choi; Kyounghee Lee; Pil Joon Seo (iScience, 2020)
Summary: Brassinosteroids (BRs) regulate a variety of physiological processes in plants via extensive crosstalk with diverse biological signaling networks. Although BRs are known to reciprocally regulate circadian oscillation, the molecular mechanism underlying BR-mediated regulation of circadian clock remains unknown. Here, we demonstrate that the BR-activated transcription factor bri1-EMS-SUPPRESSOR 1 (BES1) integrates BR signaling into the circadian network in Arabidopsis. BES1 repressed expression of CIRCADIAN CLOCK-ASSOCIATED 1 (CCA1) and LATE ELONGATED HYPOCOTYL (LHY) at night by binding to their promoters, together with TOPLESS (TPL). The repression of CCA1 and LHY by BR treatment, which occurred during the night, was compromised in bes1-ko and tpl-8 mutants. Consistently, long-term treatment with BR shortened the circadian period, and BR-induced rhythmic shortening was impaired in bes1-ko and tpl-8 single mutants and in the cca1-1lhy-21 double mutant. Overall, BR signaling is conveyed to the circadian oscillator via the BES1/TPL-CCA1/LHY module, contributing to gating diurnal BR responses in plants.